Possible vertical transmission of corona virus disease 19 (COVID-19) from infected pregnant mothers to neonates: a multicenter study. (12th December 2022) - Almaghrabi, Rana; Shaiba, Lana A.; Babic, Inas; Abdelbaky, Mona; Aljuhani, Sana Ibrahim; Omer, Magdy; Abdelmaksoud, Hisham Abdelaziz; Abdulghani, Sahar; Hadid, Adnan; Arafah, Maria A.; Omar Ali, Nagoud Mohamed; Alamir, Abdulrahman; et al.
Abstract: Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is highly contagious with various possible routes of transmission, resulting in high mortality globally. Controversy exists regarding the vertical transmission of the SARS-CoV-2 infection to fetuses of COVID-19-infected women. The aim of this study was to investigate the possibility of the vertical transmission of SARS-CoV-2 from COVID-19-infected mothers to their neonates. Materials and methods: We prospectively collected demographical and clinical characteristics of 31 COVID-19 positive pregnant women and their neonates. All mothers and neonates were tested for SARS-CoV-2 infection using the real-time polymerase chain reaction on nasopharyngeal swabs and breast milk samples. Antenatal and placental abnormalities were ultrasonically and histopathologically examined. In cord blood samples, the immunoglobins (Ig) M and IgG were estimated qualitatively. Results: The women's mean age and gestational age were 31 years and 38 weeks, respectively, with 58% undergoing an elective cesarean section. Gestational diabetes was reported in 29% of cases, 64.5% of women were medically free and only 16.12% were symptomatic. A normal antenatal ultrasound was observed in 77.42% of cases. Nine cord blood samples were positive for IgG. Villous infarction (24%), villous agglutination, and chorangiosis (51%), accelerated villous maturation (21%) and reduced and hypercoiling were reported for 6.97% of the umbilical cords. Three newborns had possible vertical transmission of SARS-CoV-2 infection, of which, two were preterm and IUFD. The third neonate was born full-term, admitted to NICU and later discharged in good health. Conclusion: Our findings support the possibility of the direct vertical transmission of the SARS-CoV-2 infection to neonates from infected mothers. Further studies with a larger sample size are required to validate the current findings.